2010
DOI: 10.1186/1471-213x-10-103
|View full text |Cite
|
Sign up to set email alerts
|

PLCγ-activated signalling is essential for TrkB mediated sensory neuron structural plasticity

Abstract: BackgroundThe vestibular system provides the primary input of our sense of balance and spatial orientation. Dysfunction of the vestibular system can severely affect a person's quality of life. Therefore, understanding the molecular basis of vestibular neuron survival, maintenance, and innervation of the target sensory epithelia is fundamental.ResultsHere we report that a point mutation at the phospholipase Cγ (PLCγ) docking site in the mouse neurotrophin tyrosine kinase receptor TrkB (Ntrk2) specifically impai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 45 publications
(72 reference statements)
2
21
0
Order By: Relevance
“…Neuron survival is normally regulated by both neurotrophins, but only BDNF is required for correct targeting and guidance. Targeting may utilize different signaling pathways downstream of the TrkB receptor than those employed in neuron survival (Sciarretta et al, 2010). In fact there is considerable evidence that not only do NT4 and BDNF function by activating different signaling mechanisms, neuron survival and targeting are mediated by differential signaling (Gartner et al, 2006; Ming et al, 2002; Minichiello, 2009; Minichiello et al, 2002; Postigo et al, 2002; Sciarretta et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Neuron survival is normally regulated by both neurotrophins, but only BDNF is required for correct targeting and guidance. Targeting may utilize different signaling pathways downstream of the TrkB receptor than those employed in neuron survival (Sciarretta et al, 2010). In fact there is considerable evidence that not only do NT4 and BDNF function by activating different signaling mechanisms, neuron survival and targeting are mediated by differential signaling (Gartner et al, 2006; Ming et al, 2002; Minichiello, 2009; Minichiello et al, 2002; Postigo et al, 2002; Sciarretta et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…These findings demonstrate that the functions of the two factors are largely interchangeable. This was surprising, because these two neurotrophic factors can activate different signaling pathway through the same Trk receptor (Berghuis et al, 2006; Bibel and Barde, 2000; Huang and Reichardt, 2003; Minichiello, 2009; Minichiello et al, 1998; Sciarretta et al, 2010). However, for the developing taste system it is primarily location and timing that dictates the function of the two TrkB ligands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These interactions were also found to be essential for survival of SGNs, as it was shown that targeted deletions of either BDNF and NT-3 (26,78) or trkB and trkC receptors (108,149,151,160) result in loss of SGNs. In addition, mice lacking both the phospholipase C␥ (PLC␥) and the Shc binding sites of trkB have recently been described producing a similar cochlear phenotype to that seen in trkB-null mice, supporting the idea that the trkB signaling pathway predominantly depends on these two docking sites (155). Taken together, the analysis of single receptor-or ligand-deficient mice initially suggested that BDNF and NT-3 specifically support the innervation of OHCs and IHCs, respectively (35,39,77).…”
Section: Axon Outgrowth and Extensionmentioning
confidence: 94%
“…Previous studies have found that GDNF signals through a unique multicomponent receptor system consisting of RET tyrosine kinase and glycosylphosphatidylinositolanchored co-receptor (GFRα1-4) in the cell membrane (9). Notably, the GDNF-TrkB signaling pathway has been proven to be involved in the transcription, translation and trafficking of proteins during neuronal and synaptic plasticity of the nervous system (10,11), and these functions are carried out by a combination of the three signaling cascades triggered when GDNF binds TrkB: the mitogen-activated protein kinase (MAPK), phosphoinositide phospholipase C-γ (PLCγ) and phosphatidylinositol 3-kinase (PI3K) pathways (10)(11)(12)(13). The brain-derived neurotrophic factor (BDNF)-PLC-γ pathway has been found to widely participate in many neuronal activities such as neurite outgrowth (14,15) and differentiation (10,16).…”
Section: Introductionmentioning
confidence: 99%